Economic Diplomacy: An Important Tool For Achieving Foreign Policy Goals - Arystankulova, Gulsara; Sheryazdanova, Kamilla; Kakenova, Galina (Opción, 2019)
This article discusses the features of the global development in the XXI century, in particular, the strengthening of the economic factor in international relations and world politics in the context of the growing interconnectedness and interdependence of states via comparative qualitative research methods. As a result, the new imperatives of modernization stipulate the necessity of perfection of tool and methods of economic diplomacy in accordance with geo-economic realities of new world order. In conclusion, the economic diplomacy as an integral component of foreign policy activity is important in the context of defining strategies for further development of the states.